Quality of care offered to HIV positive pregnant women during routine opt out HIV testing and counselling in Dedza, Malawi - Khonje Mtumbuka, Ellasy (2021)
Following a joint policy statement by the WHO/UNAIDS in 2004 and also a policy statement in the National HIV/AIDs policy of 2003, HIV Counselling and Testing is offered routinely in antenatal clinics in Malawi, known as opt out HIV testing and counselling. The aim of this study was to describe the quality of the care offered to HIV positive pregnant women during routine HIV testing and counselling at the antenatal clinic. The study utilized a descriptive exploratory design using qualitative phenomenological method and was guided by Donabedian quality conceptual framework. The study was conducted at the antenatal clinic of Dedza District hospital in the Central Region of Malawi. Twelve HIV positive antenatal women between the ages of 15-49 were purposively sampled and interviewed through in depth interviews using semi structured interview guide. In addition, a check list was also utilized to observe and examine the structure elements in HIV testing and counselling and health workers present at the time were also interviewed to verify the findings on structure attribute. Observation was also utilized to supplement the findings from the in depth interviews. Data was analyzed through thematic content analysis. The findings revealed inadequate infrastructure, lack of some necessary resources and lack of adherence to guidelines as structural issues affecting the quality of HIV testing and counselling. Women made the decision about HIV testing at home prior to visiting the antenatal clinic and were well aware of HIV and its related issues. Women were primarily motivated to get tested in order to know their status so they could protect their baby and get access to treatment and care. The findings also revealed that the right to opt out of the test was not mentioned by the providers before administering the test and there were some women who were not aware of that possibility. In addition the findings revealed some gaps in the counselling process, more especially during the pre test counselling. However the data revealed that the participants were satisfied with the care and the services provided, and emotional needs and well being of participants was well taken care of by the counselors. As a result, a majority of the participants had disclosed their status to someone especially the partner even though some of the partners had not yet gone for testing. The results of this study indicate that there are still some gaps during HIV testing and counselling especially on the structure and process attributes. Therefore there is a need to ensure quality in HIV testing and counselling services if clients are to benefit from HIV services available. Supportive supervision is necessary to ensure adherence to the guidelines by the service providers so that women receive appropriate and adequate information before and after the test to make informed decisions. In addition there is need for continued community awareness campaigns to ensure that the women have the right information on HIV and PMTCT. Availability of resources is necessary more especially test kits to ensure timely diagnosis of HIV. This is a critical issue considering the damage that the virus causes to the immunity of the person who is infected who does not begin treatment, so that the woman can benefit from timely interventions. Finally there is a need to encourage couple counselling as this will ensure that more men are tested together with their partners and provide support in preventing mother to child transmission to their partners. This will in turn contribute towards the achievement of the goals of the prevention of mother to child transmission programs and hence assist in the reduction of the maternal and neonatal mortality rates.